Contribution of al- Zahrawi (Albucasis) in the field of Pharmacy and Pharmacology with respect to his treatise Kitab al-Tasreef - Ali, Mohd Akhtar; Mohd Danish, -; Hamiduddin, - (International Journal of Human and Health Sciences (IJHHS), 2021)
Abūl-Qāsim Khalaf ibn ʿAbbās al-Zahrāwī Latinised as Abulcasis or Zahravius, lived between 936–1013 AD. He was born and raised in Al-Zahra a suburb of Córdoba (Arabic: Cortoba) in Spain. He was a famous surgeon, a talented pharmacist and a capable pharmacologist. Zahrawi is very famous for his surgical contribution, but this work explores his pharmaceutical and pharmacological contribution with respect to his treatise Kitab al-Tasreef. He served as the court physician to Caliph ʿAbd ar-Raḥmān III an-Nāṣir (912–961 AD). He wrote his famous book “Kitab al-Tasreef li-man ‘ajaza ‘an al-ta’lif” (The Arrangement of Medical Knowledge for one who is not able to compile it) around the year 1000 AD after fifty years of clinical experience. This book is also a chief source for indicating pharmaceutical contribution of al-Zahrāwī apart from the field of surgery. Twenty seven volumes, from Volume 3 to 29, of thirty volumes of the book Kitab al- Tasreef are related to Unani pharmacy and pharmacology. Ibn Abī Uṣaybiʿa (1203-1270 AD) remarked him only as an expert of pharmacy and pharmacology. Al-Zahrāwī devoted his entire life and genius to the advancement of pharmacy, medicine and surgery. He sketched a few drawings of pharmaceutical instruments and mentioned their use in his book. Significant pharmaceutical contributions of al-Zahrāwī are reflected by him through Kitab al-Tasreef which has not been highlighted, there is need to evaluate and emphasize the pharmaceutical contributions of al-Zahrāwī. This review is an attempt in this direction. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 276-285